Examining the factors influencing secondary school students’ motivation in learning Islamic education - Adesina Muhammed-Lawal, Adam; Abd Rashid, Adnan; Badrasawi, Kamal J I (2017)
Islamic Education aims, ultimately, to produce a good man in all aspects of his personality. This study aims to identify secondary school students’ motivation in learning Islamic education subject and to investigate the factors influencing their motivation. The descriptive cross-sectional survey design was utilized. One hundred and seventy (170) students were selected using a non-random, quota sampling procedure from an International Islamic school in Malaysia to answer a 32-item questionnaire. The items targeted four constructs: Student-motivation (SM), Parentalinfluence (PI), Pedagogy (P) and Teacher-morality (TM) using a 5-point Likert scale. Descriptive statistics (Mean and Standard Deviation) and Pearson product-moment correlation coefficients were used for the analysis of the data. The results show that students’ motivation to learn Islamic education subjects was relatively high. Moreover, there were significant relationships between the factors (Parental Influence (PI), Pedagogy (P) and Teacher-Morality (TM) and Students-Motivation (SM). The study suggests that there is room for improvement in student-motivation to study Islamic education. To this end, teachers should vary their teaching methods. Lastly, qualitative research methodology is recommended for more in-depth information.